BUDAYA DAN FUNGSI DALAM LEGENDA GUA TAN TIK SIU DI DESA SUMBERAGUNG KECAMATAN REJOTANGAN KABUPATEN TULUNGAGUNG - Tsalits Abdul Aziz Alfarisi (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2019)
Literature is an expression of feeling and of thought written by contextual value of a language. It refers to the concept of oral or folk literature which includes the literature expression of society’s culture passed on upon descend and through spoken word. The legend of Tan Tik Siu cave is one of oral literature originated from Tulungagung which grew and expanded in Sumberagung village Rejotangan subdistrict. The originality and cultural value of the phenomenon are feasible to investigate due to its uniqueness. There is a cycle when the society should and should not do some rituals in the cave. Thus, they should not do the ritual every day. It is believed that there will be a danger for Sumberagung villagers whenever they break the conviction. The problem of the study focused on how are the cultural values and its functions for the society. A descriptive qualitative approach is employed through observation, interview, audio-recording and note-taking. The analysis of cultural value suggested four kinds of cultural values including: (1) magic value, especially the society’s belief on pesugihan /a particular magic, (2) behavior value applied to the surrounding society, and (3) religious value. The result function analysis found four kinds of functions which cover: (1) projection system as a one’s thoughts on the future doing, (2) validation instrument of cultural research organization (3) education instrument (4) entertainment instrument